Introduction - Z. Izarra, Laura P. (ABEI Journal, 2003)
This Special Issue of ABEI Journal – The Brazilian Journal of Irish Studies is a selection of papers presented at the conference, entitled “Interrelations: Irish Literatures and Other Forms of Knowledge”.